Ibadah Adalah Pangkalan Misi di Jemaat Gmim Zaitun Motoling 1 Minahasa Selatan - Yessy Kenny Jacob (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims and benefits of this research are: (a) Finding the factors that cause the disconnect between worship and the mission of the church members in the community; (b) find a concrete form of worship as a mission base for the church members, namely worship as worship to the Lord God as well as a test of missionary actions from church members; and (c) as a contribution to the thoughts of churches in fulfilling their mission to empower church members to be able to witness and serve in the community. Efforts to prove the hypothesis were carried out through research using various methods, namely: library research, field observations, interviews, experiments. It is immediately apparent that the research approach is more sociological. The research location is in the Motoling 1 Congregation in the Motoling Region. Motoling was chosen as the research location because it is seen from the point of view of the Church's mission in the community, which cannot ignore the agricultural sector. This sector absorbs the most labor in Indonesia in general and Minahasa in particular.